IMPROVING ENGLISH VOCABULARY THROUGH PLAYING GAME OF HEAVEN HELL FOR CHILDREN - Fitrah Yuliawati; Satik Satik (PROJECT (Professional Journal of English Education), 2022)
The aim of this study is to help the student easier to remember or memorize the new vocabulary through heaven hell game in study English. Basically, heaven hell is a pleasure method and it is easy to implement by the teacher to increase student’s memory in memorizing new vocabulary and also it is effective to use in teaching learning process. This study using qualitative research by designing, implementing, and evaluating actions collaborative and participatory that aim to improve the quality process in the classroom through an action (treatment). Knowing English vocabulary is very important for children. The students’ skill in English vocabulary by using heaven hell game method had improved. It could be showed from the result of pre-test and post-test. By the student’s mean score of post-test in cycle II is higher than mean score of post-test in cycle I (81,25) > (75,93). The researcher could say that heaven hell is recommended method in teaching English for children. This learning method improved the students’ skill in English vocabulary.    Keywords:  Vocabulary, Heaven Hell, Method, Kindergarten